1997
DOI: 10.1007/bf02054978
|View full text |Cite
|
Sign up to set email alerts
|

Value of carcinoembryonic antigen monitoring in curative surgery for recurrent colorectal carcinoma

Abstract: CEA-driven surgery is useful in selected patients and can produce long-term survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
1
23
0
4
Order By: Relevance
“…This would suggest that serial tumour marker assessments should be performed in all patients during follow-up irrespective of the levels before resection of the metastases. While the role of CEA in screening following resection of colorectal liver metastases is welldocumented (Hohenberger et al, 1994;McCall et al, 1994;Paganuzzi et al, 1994;Lucha et al, 1997;Novell et al, 1997;Hocking and Morris, 1998;Wichmann et al, 2000;Ishizuka et al, 2001), there is less published evidence on the use of CA 19-9 (Ishizuka et al, 2001;Carpelan-Holmstrom et al, 2002). In the present study, CEA and CA19-9 were found to be of similar value and complementary in the detection of recurrence following liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that serial tumour marker assessments should be performed in all patients during follow-up irrespective of the levels before resection of the metastases. While the role of CEA in screening following resection of colorectal liver metastases is welldocumented (Hohenberger et al, 1994;McCall et al, 1994;Paganuzzi et al, 1994;Lucha et al, 1997;Novell et al, 1997;Hocking and Morris, 1998;Wichmann et al, 2000;Ishizuka et al, 2001), there is less published evidence on the use of CA 19-9 (Ishizuka et al, 2001;Carpelan-Holmstrom et al, 2002). In the present study, CEA and CA19-9 were found to be of similar value and complementary in the detection of recurrence following liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, a considerable variation in prognosis has been demonstrated within each stage (Jass et al, 1987;Newland et al, 1987) and some patients with Dukes' stage B have a poorer prognosis than patients in Dukes' C. Several studies have been performed to find new biochemical markers in order to identify patients at high risk for recurrence, who might be candidates for additional therapy after surgery. There are numerous reports on CEA in screening and follow-up of patients with colorectal cancer, but this marker seems to be of limited clinical use (Kievit and Van der Velde, 1990;Virgo et al, 1995;Lucha et al, 1997). Nevertheless, the most frequently used marker is still CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up regimens after resection for primary colorectal cancer in general consist of periodic interval history, physical examinations and endoscopic surveillance. The usefulness of analysing consecutive serum carcinoembryonic antigen (CEA) levels has been questioned (Kievit and Van der Velde, 1990;Virgo et al, 1995) but CEA is still used as an eventual predictor of residual disease or metastases (Lucha et al, 1997).…”
mentioning
confidence: 99%
“…After surgical removal of a primary tumour, increasing circulating CEA levels often precede the development of metastases, especially liver metastases (Lucha et al, 1997). Thus, there is a clear relationship between circulating CEA levels and metastases, but it is impossible to demonstrate in humans a connection between cause and effect.…”
mentioning
confidence: 99%